False positive PET scan of hereditary leiomyomatosis and renal cell cancer: A case report - Heather M. Zimmerman, BSN; Ralina Karagenova, MS; Bao Xin Liang, BS; David J. Elpern, MD; Douglas W. Johnson, MD (Radiology Case Reports)
Hereditary leiomyomatosis and renal cell cancer (HLRCC) is an inherited condition, predisposing patients to develop cutaneous or uterine leiomyomas along with aggressive type 2 papillary renal cell carcinoma (RCC). Patients are routinely monitored for cancer and metastases. A 62-year-old man with HLRCC presented to the dermatology clinic, referred by oncology because he potentially had metastatic (RCC) based on a recent PET scan. The patient’s medical history revealed stage 1 papillary RCC of the right kidney and mid-left kidney (both surgically removed) and multiple cutaneous leiomyomas. Physical exam revealed multiple nodules on the abdomen, lower extremities, and left shoulder. PET scan showed a hypermetabolic cutaneous lesion in the superior aspect of the left shoulder, concerning for metastatic disease. A punch biopsy of the 9 mm left shoulder nodule was performed. Microscopic evaluation showed proliferation of spindled cells arranged in intersecting fascicles within the dermis. The spindle cells had cigar-shaped nuclei with abundant eosinophilic cytoplasm. There was no cytologic atypia or increased mitotic activity. The cells were positive for desmin immunostain. The patient was offered an excision or biopsy of the benign leiomyoma, and he requested a biopsy. He was advised to seek further treatment if the lesions became symptomatic. Patients with HLRCC may have benign cutaneous leiomyomas that are suspected of being metastatic disease, with false positive PET scans. Care should be taken to counsel patients on the potential for false-positive PET scans in this condition, and screening should be conducted in the case of multiple cutaneous or uterine leiomyomas.